Teaching for the Lifespan : Successfully Transitioning Students With Learning Differences to Adulthood. - Reiff, Henry B. (SAGE Publications, 2015)
Your step-by-step guide to successful transition planning Finally, here's a practical guide that makes transition planning easier. Backed by the latest research in learning and development, Teaching for the Lifespan provides you with the pedagogical best practices to promote your students' strengths for life-long success. You'll benefit from: A deep understanding of the educational, vocational, social, and emotional dimensions of adulthood for students with learning differences Techniques to help students with learning differences develop an awareness of proactive behaviors Strategies to help.